Takotsubo Cardiomyopathy “Variations on a Theme” - Kjell Bogaard; Diego A. M. Odekerken; Albertus J. Voogel (Case Reports in Cardiology)
Takotsubo Cardiomyopathy (TTC) is a fairly new diagnosis in the cardiologist's repertoire. It can present itself in multiple different forms. We describe three cases of TTC with different etiologies illustrating the broad spectrum of presentations.